Closure of oroantral fistula with the bichat ball (Research, Society and Development, 2022)
Oral communication (CBS) is described as a direct access between the maxillary sinus and the oral cavity. Commonly, it is located in regions that interfere with the maxillary sinus, and may also be caused by cystic disease, infections, tumors or trauma. Therefore, the objective of this study is to describe the closure of the oroantral fistula with the bichat ball. This is a qualitative literature review with descriptive analysis, developed through the search strategy through the DeCS: “fat body”, “oral fistula” and “maxillary sinus” in electronic databases such as SciELO and PubMed. The inclusion criteria were established, publications in Portuguese and English, with a time limit of the last 12 years. The treatment of CBS must be immediate, to prevent complications and consequently obtain a better prognosis. The most common aggravations of this communication are maxillary sinusitis, when untreated it can lead to the development of sinus diseases. The treatment for closure of oroantral fistula with the bichat ball proved to be effective, easy to perform and had a good prognosis.